Evaluation Of BIBR1532 And ATRA Combination In NB4 Cell Line - Mohammad Sabbaghi; Ahmad Kazemi; Saeed Hassani; Kamran Alimoghaddam; Ardeshir Ghavamzadeh; Seyed Hamidollah Ghaffari (Tehran University of Medical Sciences, 2014)
Background and Aim: Acute promyelocytic leukemia (APL) is a distinct type of leukemia which is caused due to a blockage in myeloid cells normal maturation. The most important therapeutic strategies include the use of ATRA and Arsenic trioxide. Although ATRA is generally well tolerated, some patients develop Retinoic acid syndrome. Some of the symptoms of this syndrome are directly or indirectly related to elevated WBC counts. This study aims to determine the effect of ATRA and BIBR1532 combination on WBC count as a factor leading to the formation of ATRA syndrome. Materials and Methods: To investigate the effect of BIBR1532 and ATRA combination, NB4 cells were cultured in the presence of 30μ M and 1 μM densities of the drugs. To study the effect of drugs on living cells count, proliferation activity, and metabolic activity of the cells, Trypan blue, Brdu and MTT tests were used, respectively. Results: The results of Trypan blue, MTT and Brdu suggest that the combination of ATRA and BIBR1532 is more effective than ATRA alone on the reduction of viable cell count, metabolic activity and proliferation of leukemic cells in the first five days of treatment. Conclusion: The results suggest that the combination of ATRA and BIBR1532 is probably more effective in the treatment of APL patients. It seems that such improvement in results is more obvious especially among the patients who are at a higher risk of ATRA syndrome.